The effect of distributed leadership on teacher self-efficacy in Mainland China: A systematic review (2019–2025) - Cheng Zhang; Bity Salwana Alias; Mohd Norazmi Nordin (Environment and Social Psychology, 2025)
This systematic review synthesizes empirical studies published between 2019 and 2025 on the relationship between distributed leadership (DL) and teacher self-efficacy (TSE) in Mainland China. A total of 8,742 records were retrieved from major academic databases, with 10 high-quality studies selected through a PRISMA-guided screening process. The findings reveal a consistently positive association between DL and TSE, mediated by factors such as teacher collaboration, professional trust, teacher leadership, and ICT integration. Moderating influences, including interpersonal trust, school culture, and regional disparities, underscore the contextual complexity of DL within China’s dual centralized governance structure and high power-distance culture. This review clarifies the mechanisms through which DL supports TSE and offers culturally responsive recommendations. It advocates for embedding DL into teacher professional development, strengthening departmental collaboration, increasing teacher leadership participation, and incorporating indigenous philosophies such as Wang Yangming’s “unity of knowledge and action” to enhance intrinsic teacher agency. Overall, this review enriches the cultural lens of educational leadership and offers actionable strategies for fostering teacher professional growth.